2006
DOI: 10.1103/physrevb.74.165308
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effect in core-shell structured silicon-germanium nanowires

Abstract: First-principles density functional theory has been employed to study the composition dependent quantum size effect in a series of silicon-germanium core-shell structured nanowires with the diameters ranging from 0.5 to 3.2 nm. Analysis of the calculated band gap energies in Si-core/Ge-shell and Ge-core/Si-shell structured nanowires shows a nonlinear composition dependence for nanowires with fixed diameter ͑fixed total number N = N Core + N Shell of Si and Ge atoms in the unit cell͒. In contrast, for nanowires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 61 publications
(29 reference statements)
6
76
0
1
Order By: Relevance
“…In recent years, various methods of synthesis have been developed, [17][18][19][20] which guarantee a precise control of composition, morphology, and electronic properties. Several theoretical [21][22][23][24][25] and experimental 5,12,26,27 studies have shown that the electronic, transport, and optical properties of SiGe NWs, like other nanostructures, are strictly related to their low dimensionality and to the quantum confinement effect ͑QCE͒. [28][29][30] Moreover, they offer, unlike the corresponding pure single material NWs, the possibility of modulating band structure, band gap, and optical spectra by changing not only the size of the material but even the composition and the geometry of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various methods of synthesis have been developed, [17][18][19][20] which guarantee a precise control of composition, morphology, and electronic properties. Several theoretical [21][22][23][24][25] and experimental 5,12,26,27 studies have shown that the electronic, transport, and optical properties of SiGe NWs, like other nanostructures, are strictly related to their low dimensionality and to the quantum confinement effect ͑QCE͒. [28][29][30] Moreover, they offer, unlike the corresponding pure single material NWs, the possibility of modulating band structure, band gap, and optical spectra by changing not only the size of the material but even the composition and the geometry of the system.…”
Section: Introductionmentioning
confidence: 99%
“…They are promising materials for building blocks of field effect transistors [24][25][26]. Several experimental [27,28] and theoretical [29][30][31] investigations have been performed to study of the quantum confinement effects in the Si-Ge core shell nanowires. For instance the Peng et al [22] have studied the band structure properties of the Si-Ge core-shell nanowires in different situations of applied uniaxial strain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One dimensional (1D) semiconductor nanostructures are currently the subject of material study due to their promising applications in the field of nano-optoelectronics, sensors and environmental cleaning, as well as their scientific interest for quantum size effect [1][2][3][4][5]. Compared with other materials, group III-nitride nanostructures have been intensively studied because of their wide band-gap ranging from 0.7 eV for InN to 6.2 eV for AlN, and the intriguing properties behind them [6][7][8].…”
Section: Introductionmentioning
confidence: 99%